Examination of Hedonic Consumption Themed Advertising Images Using Eye-Tracking - Emül, Selin; Yücel, Atilla (Ebru Bagci, 2021)
In today's developing conditions, the consumption habits of people are changing. As consumption habits change, individuals shift their shopping from utilitarian consumption to hedonic consumption, ie pleasure-oriented purchasing behavior, which is influenced by rational factors due to various reasons such as environment, psychological, escaping from the stress of daily life, similarity or separation. Neuromarketing is also a process that reveals the subconscious thoughts, feelings and desires that shape the ideas you think, the decision to purchase. With this study, starting from how the brain reacts to consumers' preference for products with a sense of pleasure in daily life; Combining hedonic consumption and neuromarketing, the reactions of consumers to advertisements with hedonic content and how they perceive these ads are examined experimentally with Eye-Tracking method, which is one of the neuromarketing techniques. In this study, 7 visuals that were turned into a 5-second slide for Hedonic consumption of Algida Magnum brand were displayed. With the Eye-Tracking analysis method, the eye movements of the participants were analyzed and the data regarding their reactions to these advertising images were analyzed and interpreted. In addition to contributing to the theoretical neuromarketing and hedonic consumption literature, this study also features a new study among academic studies. In terms of implementation, it is a work that guides the experimental studies to be done next. © 2021, Ebru Bagci. All rights reserved.
Hedonik Tüketim Temali Reklam Görsellerinin Eye-Tracking İle İncelenmesi
Keywords: Consumer Behavior; Eye-Tracking Method; Hedonic Consumption; Marketing; Neuromarketing